1992
DOI: 10.1016/s0022-5347(17)37126-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Trial of Oral Bropirimine in Superficial Bladder Cancer

Abstract: A total of 34 patients with measurable superficial transitional cell cancer of the bladder entered into a phase 1, nonrandomized, noncomparative trial to assess the toxicity of the oral interferon inducer bropirimine. Of the patients 26 were also evaluable for response. The toxicity of bropirimine was minimal. At the 3-month evaluation 6 patients had experienced complete regression of tumor and had negative cytology studies, and 2 had partial responses. The majority of complete responses were in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…In an escalating-dose study reported by Sarosdy et al [55], the treatment regimen was well tolerated, toxicity was mild among the 32 patients evaluable for side effects and induced complete responses in 5 of 10 cases of Cis. (Daily doses of bropirimine 3.0 g or more for 3 con secutive days and repeated weekly for 12 weeks.)…”
Section: Oral Treatmentmentioning
confidence: 91%
“…In an escalating-dose study reported by Sarosdy et al [55], the treatment regimen was well tolerated, toxicity was mild among the 32 patients evaluable for side effects and induced complete responses in 5 of 10 cases of Cis. (Daily doses of bropirimine 3.0 g or more for 3 con secutive days and repeated weekly for 12 weeks.)…”
Section: Oral Treatmentmentioning
confidence: 91%
“…NK cell and macrophage populations are increased, as are interleukin-2 (IL-2) and IL-2 receptors, and tumor necro sis factor (TNF) [4,5], Bropirimine is active against a number of viral illnesses and several different tumors, including human bladder cancer [6], In bladder carcino ma in situ, bropirimine has been shown to convert biop sies and bladder wash cytologies from malignant to nonmalignant in approximately 50% of patients, including some who have failed to respond to intravesical bacillus Calmette-Guérin (BCG) [7,8], To test for bropirimine activity in prostate cancer, it was administered to rats carrying subcutaneously injected PAIII or Dunning MAT-LyLu cancer cells [9], Both are androgen-independent rodent prostate cancer cell lines. PAIII was derived from a spontaneous prostate cancer in Lobund-Wistar (LW) rats, and has been used to screen…”
Section: Introductionmentioning
confidence: 99%
“…However, single agent efficacy of bropirimine against carcinoma in situ was identified in the pilot clinical trials as well as subse quent phase II studies [7,8], Attempts at immunotherapy in prostate cancer are not new. Several nonspecific immunostimulants have been tried, including BCG (both systemically and intraprostat ic), Corynebacterium parvum, levamisole, and interferon.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical trials with the oral interferon-inducing agent, bropirimine, low-level activation of the interferon system, even in the absence of detectable interferon production, was shown to produce some clinical responses in bladder cancer (Rios et al, 1986;Sarosdy et al, 1992). Therefore, it is possible that imiquimod administered at low doses may develop a role in adjuvant therapy or in long-term anticancer treatments.…”
Section: Discussionmentioning
confidence: 99%